KARAKTERISTIK PENDERITA FRAKTUR PADA LANSIA RAWAT INAP DI RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2011-2012 - Cindy Natasia Sinukaban; drh. Hiswani, M.Kes; Drs. Jemadi,M.Kes (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Fracture, by definition is a condition where discontinuity occur on bone tissue that basically involves direct/indirect trauma. (World Health Organization) WHO reported 200 million people older than 40 years old on 2012 experienced osteoporosis induced fracture. Elder fracture patient that hospitalized in Santa Elisabeth Medan Hospital on 2011-2012 reaches 107 patient. To understand characteristics of elder patients with fracture that hospitalized at Santa Elisabeth Hospital on 2011-2012, a descriptive study with case-series design have been conducted. Population is sample of study contained 107 data (total sampling). Data were collected from medical record and analyzed using chi-square and t-test. Proportion of patients with fractures by highest sociodemographic found in 45-59 years old (55.1%), female (52.3%), Batak ethnicity (74.8%), Protestant (59.8%), has academic degree (43.9%), housewives (25.2%), married (93.5%), from Medan (59.8%), traffic accident (57,9%), closed fracture (86.0%), on pelvic region (29.9%), treated by operation (63.6%), 7 days length of hospitalization, and recover/outpatient (83.2%). No difference between age in proportion to location of fracture (p=0.110). There was difference between age in proportion to cause of fracture (p=0.000). There was difference between gender in proportion to the cause of fracture (p=0.030). No difference between gender in proportion to type of fracture (p=0.112). There was difference between medical treatment in proportion to type of fracture (p=0.045). No difference between causes of fracture in proportion to location of fracture (p=0.131). No significant difference between average length of hospitalization to type of fracture (p=0.830). No significant difference between average length of hospitalization to medical treatment (p=0.069). Early prevention should be done by high risk group of osteoporosis. Higher awareness and avoiding fall risk factors should be done by patients in order to prevent future fractures. Santa Elisabeth Hospital is suggested to add fracture complications and type of fragments in medical record. Keywords: Fractures, Elderly, Characteristics